Specifičnost rehabilitacije starostnikov - Turk, Zmago (Zdravniški vestnik, 2008)
Many of demographic changes occurred in the past decade and the share of people over 65 years of age in Europe is already exceeding 17%. The elderly are marked with multimorbidity and greater frequency of injuries which go hand in hand with decrease in functional abilities and daily living quality. Degenerative diseases, chronic diseases, diabetes, arteriosclerosis, and osteoporosis require different access to the health care system and there is a need for establishing a biosociomedical program for the elderly, which will encompass care from home care through out to the institutionalised care. Injuries and chronic diseases, as well as changes of the musculoskeletal system require both, social and medical rehabilitation. In hospitals, various methods of physical medicine and rehabilitative services are used according to the multimorbidity of a certain patient and contraindications. Most common injuries are shaft fractures, osteoporothic vertebra fractures and hip fractures. The current health treatment includes surgery, early medical rehabilitation and home care. CVDs require a special form of rehabilitation, from early medical rehabilitation, immediately after the cerebrovascular insult, throughout to verticalisation, spa treatment and home care. Oncological patients and palliative care for elderly require special attention in the rehabilitation program. Those patients are in need of nursing, preventive and supportable physiotherapy and the comprehensive rehabilitation program that includes the civil society and family, tries to maintain the ability of independent daily living.
Keywords: Aged; Fractures, Bone; Geriatrics; Geriatrija; gerontologija; Kost, zlomi; Ostareli; poškodbe; Rehabilitacija; rehabilitation; starostniki; therapy; vocational rehabilitation; zdravljenje